Building high performing coach-athlete relationships: The USOC`s National Team Coach Leadership Education Program (NTCLEP) - Ferrar, P.; Hosea, L.; Henson, M.; Dubina, N.; Krueger, G.; Staff, J.; Wade, G. (International Sport Coaching Journal, 2018)
The purpose of the present article is to share the design and impact of a coach-athlete relationship coach education seminar. The seminar is part of the United States Olympic Committee`s (USOC) National Team Coach Leadership Education Program (NTCLEP). Development and delivery of the seminar is facilitated by The People Academy (www.people.academy). Impact results from participation in this seminar are drawn from coaches and athletes from USA Archery and USA Cycling. The article is organized into three sections. In the first section an overview of the coach-athlete relationship building component of the USOC`s high performance coach education program is provided. Two case summaries are then presented on the impact of the program on coach-athlete relationships and athlete performance. The third and final section is used to offer suggestions for future coach education initiatives and coaching strategies aimed at enhancing coach-athlete relationships.